The steroid metabolome of pregnancy, insights into the maintenance of pregnancy and evolution of reproductive traits. (15th May 2021) - Conley, A.J.; Loux, S.C.; Legacki, E.L.; Stoops, M.A.; Pukazhenthi, B.; Brown, J.L.; Sattler, R.; French, H.M.; Tibary, A.; Robeck, T.R.
Abstract: Modes of mammalian reproduction are diverse and not always conserved among related species. Progesterone is universally required to supports pregnancy but sites of synthesis and metabolic pathways vary widely. The steroid metabolome of mid-to late gestation was characterized, focusing on 5α-reduced pregnanes in species representing the Perissodactyla, Cetartiodactyla and Carnivora using mass spectrometry. Metabolomes and steroidogenic enzyme ortholog sequences were used in heirarchial analyses. Steroid metabolite profiles were similar within orders, whales within cetartiodactyls for instance, but with notable exceptions such as rhinoceros clustering with goats, and tapirs with pigs. Steroidogenic enzyme sequence clustering reflected expected evolutionary relationships but once again with exceptions. Human sequences (expected outgroups) clustered with perissodactyl CYP11A1, CYP17A1 and SRD5A1 gene orthologues, forming outgroups only for HSD17B1 and SRD5A2. Spotted hyena CYP19A1 clustered within the Perissodactyla, between rhinoceros and equid orthologues, whereas CYP17A1 clustered within the Carnivora. This variability highlights the random adoption of divergent physiological strategies as pregnancy evolved among genetically similar species.